2017
DOI: 10.3906/sag-1602-86
|View full text |Cite
|
Sign up to set email alerts
|

Nitroglycerin challenge induces lateralized headache in nasociliarynerve-ligated rats: implications for chronic migraine

Abstract: Background/aim: Chronic migraine is a common debilitating disease with limited treatment options. We aimed to develop a novel model for chronic migraine by ligating the nasociliary nerve (NCL) and administering nitroglycerin (NTG) to exacerbate acute headache attacks. Materials and methods: Exacerbation of the headache was induced by NTG (10 mg/kg, subcutaneously) administered to male Wistar rats (n = 36) 14 days following unilateral NCL. Cutaneous and cold allodynia was tested using Von Frey (VF) filaments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Thermal allodynia can be measured with different methodologies including the Hargreaves' test (73), based on applying a heat stimulus to the hind paws or tail of the animal to measure their withdrawal latency; and the acetone evaporation test, which measures the aversive behaviors elicited by evaporative cooling both in cephalic or extracephalic regions (74). These tests have been used in preclinical models of migraine, where the administration of nitroglycerin and algogenic substances have shown to increase thermal allodynia (67,68), and the nasocilary nerve ligation to increase sensitization to acetone evaporation (75).…”
Section: Use Of Allodynia As a Readout Of Migraine-like Pain In Preclinical Modelsmentioning
confidence: 99%
“…Thermal allodynia can be measured with different methodologies including the Hargreaves' test (73), based on applying a heat stimulus to the hind paws or tail of the animal to measure their withdrawal latency; and the acetone evaporation test, which measures the aversive behaviors elicited by evaporative cooling both in cephalic or extracephalic regions (74). These tests have been used in preclinical models of migraine, where the administration of nitroglycerin and algogenic substances have shown to increase thermal allodynia (67,68), and the nasocilary nerve ligation to increase sensitization to acetone evaporation (75).…”
Section: Use Of Allodynia As a Readout Of Migraine-like Pain In Preclinical Modelsmentioning
confidence: 99%
“…Stimulation with the paintbrush is repeated three times, at least 3 min in-between, and the average of three scores are calculated. Brush allodynia is used in neuropathic pain models, and chronic migraine model developed by nasociliary nerve ligation [46].…”
Section: Sensory-discriminative Aspectsmentioning
confidence: 99%
“…Akcali et al provided a chronic migraine animal model with nasociliary nerve ligation in rats and provoked lateralized headache attack by NTG. In the study, NTG administration increased acetone sensitivity in the forehead only in nasociliary nerve ligated side [46]. In a NTG-induced mouse model of chronic migraine, the duration of withdrawal responses to acetone in the facial region were significantly increased in mice treated with NTG compared to control [52].…”
Section: Sensory-discriminative Aspectsmentioning
confidence: 99%
“…Using the Hargreaves assay, acute nitroglycerin [84] and chronic administration of algogenic substances increased thermal sensitivity [83, 165]. Furthermore, a different model of chronic migraine, nasocilary nerve ligation in rats, exhibits a lateralized sensitization to acetone following nitroglycerin in the forehead ipsilateral of nerve ligation [173]. One important differentiation is that behavioral studies have also shown differential response to mechanical and thermal allodynia, highlighting the complexity of trigeminal pain processing.…”
Section: Experimental Readouts: Behavioral Assaysmentioning
confidence: 99%